MODEL SINKRETISME ISLAM DAN KEJAWEN: KAJIAN HISTORIS-FILOSOFIS ATAS SERAT SASANGKA JATI - Abdullah Safiq (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
This study aims to examine the model of Islamic syncretism and variants ofKejawenteachings in Indonesia. Using a qualitative approach, based on historical-philosophical data analysis of the Sasangka Jatimanuscripts,completed within-depth interviews and observations on the living and religious practices of the Pangestufollwoers in Tulungagung, East Java, the results of the study indicate that there is a pointof similarities and differences between the essence of "theIslamic pillars " and "Jalan Rahayu" contained inthe book of Sasangka Jati. The equality of the essence of 'IslamicPillars ' and "Jalan Rahayu", can be seen from the creed, prayer, thanksgiving, fasting, and pilgrimage. From here then the insight of thinking of human beings becomes widelyopen. So that, the true knowledge can be ascantilever for religion. Spiritual awareness used to be a guide toknowledge, with the main goal being to obtain or attain the true sense of awareness.